My brother Bert - Hughes, Ted, 1930-1998 (Farrar Straus Giroux, 2009)
Illustrations and rhyming text portray a hobby gone awry, as Bert's collection of exotic pets seems on the verge of breaking into a quarrel, and perhaps a rumpus, as well.